The impact of climate transition risks on financial stability: A systemic risk approach - Javier Ojea-Ferreiro; Juan Carlos Reboredo; Andrea Ugolini (European Commission, 2022)
Transitioning to a low-carbon economy involves risks for the value of financial assets, with potential ramifications for financial stability. We quantify the systemic impact on financial firms arising from changes in the value of financial assets under three climate transition scenarios that reflect different levels of vulnerability to the transition to a low-carbon economy, namely, orderly transition, disorderly transition, and no transition (hot house world). We describe three systemic risk metrics computed from a copula-based model of dependence between financial firm returns and financial asset market returns: climate transition expected returns, climate transition value-at-risk, and climate transition expected shortfall. Empirical evidence for European financial firms over the period 2013-2020 indicates that the climate transition risk varies across sectors and countries, with banks and real estate firms experiencing the highest and lowest systemic impacts from a disorderly transition, respectively. We find that default premium, yield slope and inflation are the main drivers of climate transition risk, and that, in terms of capital shortfall, the cost of rescuing more risk-exposed financial firms from climate transition losses is relatively manageable. Simulation of climate risks over a five-year period shows that disorderly transition can be expected to imply significant costs for banks, while financial services and real estate firms remain more sheltered.
Keywords: C32; C58; G01; G20; G28; 330; Climate risks; financial stability; systemic risk; copulas